Management of Yauvanapidika Through Shamanaushadhi (International Journal of Ayurveda and Pharma Research, 2025)
The face is universally recognized as an essential element of emotional expression and personal identification. The presence of acne can notably impact an individual’s self-esteem, especially in social interactions. In Ayurvedic literature, Yauvana Pidika, as described by various Acharyas, exhibit features similar to acne vulgaris. Yauvanapidika, due to its minimum causative factors, signs and symptoms and less severity is mentioned as one of the Kshudrarogas in Ayurveda Samhitas. A 23-year-old female patient who was apparently normal before six months developed multiple pus-filled acne on her forehead and both cheeks associated with pain and redness had consulted the outpatient department. She was having regular tea consumption twice a day, a mixed diet, and excess consumption of sugars, oily, and junk food. She consulted other contemporary medical systems as well, but didn’t find any relief. She was under Ayurvedic management for one month and felt very satisfied with the results. In this paper, successful management of this case with Shamana modalities is highlighted, which will be documented evidence for future case studies.